TEACHING AND LEARNING METHODS - S. R. GUNERATHNE; FMMT MARIKAR (Social Sciences and Education Research Review)
This article concerns itself with the 4-celled matrix of the, 4 MAT and Kolb Cycle, very specifically with its experiential domain, which deals with preferences and phobias generated by life experiences. An Equanimeous understanding of such emotions are of vital importance to students for the purpose of eliminating destructive biases that limit their design potential. In order to help students, access such experiences, which often times have been relegated to the unconscious due to their painful nature, this piece have had recourse to Gregory Ulmer's "My story". This is a literary invention that helps trace positive or negative life experiences recurring as themata in an individual's family history, community history, entertainment sphere and career field. An awareness of such themata, which predispose an individual to resort to certain practices to the exclusion of others, is a prerequisite in architectural design since exclusionary approaches tend to deprive designs of their complexity and multifacetedness. Furthermore, architects are the arbiters elegantiae, aesthetic decision makers, for all professions and persons from all walks of life. As such, a sympathetic understanding of the reasons for one's biases or preferences, which is facilitated by the rapprochement of our irrational unconscious with our conscious mind, helps architects design with an open mind and a sense of freedom. In classroom teaching of design theory, teacher superimposed Ulmer's Mystory on the Kolb Cycle's experiential domain, to create a device that helps students get in touch with the experiences of their formative childhood years as a precondition for the understanding of their biases. The creative use of biases as themata in a person's life facilitates the fleshing out of the spatial genome.